Space-ground integrated satellite communication network architecture for global energy internet - Yongliang LI; Xu’an LI; Jie TONG; Yuqing LEI; Huixia DING; Junfeng LAN (Dianxin kexue)
The system monitoring and scheduling,time service and synchronization,object location and other businesses of global energy internet all need reliable communication networks,which are able to provide wide area coverage and ubiquitous flexible access services.According to the requirement,various new businesses and their data features with the background of the global energy interconnection were firstly analyzed,and then the unique characteristics of satellite communication technology and how it highly accords with the demands of the global energy internet were discussed.Then a space-ground integrated network architecture by the integration of satellite communication networks was presented.Based on IP technology,each network layer interconnects through various communication links,including satellite to satellite,space to ground,ground cable,wireless link,etc.,and then constitute an integrated network system with excellent global coverage performance.